Dark tetrad personality types and sexual behaviours amongst African students - Baloyi, Valeria (My University, 2019)
The present study investigated the gender moderated relationship between the dark tetrad personality types and sexual behaviours among African university students. Two studies were conducted using conveniently selected samples from two universities in Limpopo, South Africa. Both studies were quantitative in nature using a cross-sectional research design. An integrative theoretical approach was utilized in the conceptualization of the studies, and data was analyzed using structural equation modeling (SEM). The first study (N = 261) determined the relationship between the dark tetrad personality types and sexual behaviours conceptualized as infidelity, sexual aggression, and sociosexuality. It was only sadism that had the capacity to predict infidelity and SOI-R desire. Regarding moderation, the results showed that gender only moderates the associations between Machiavellianism and SOI-R behaviour, psychopathy and SOI-R attitude, and sadism and infidelity. The second study (N = 275) examined if the relationship between the Dark Tetrad personality types and socio-sexuality would be mediated by adversarial sexual beliefs (ASB) and ambivalent sexism (benevolent [BS] and hostile sexism [HS]). Results showed that the relationship between sadism and SOI-R behaviour and desire, Machiavellianism and SOI-R behaviour and desire were fully mediated by BS, and the association between sadism and all the SOI-R components, Machiavellianism and all the SOI-R components, and psychopathy and all the SOI-R components were fully mediated ASB. Additionally, gender only moderated the ASB mediated associations between sadism and SOI-R behaviour, and sadism and SOI-R attitude. Ultimately, the study advances recommendations for future studies.
Thesis (Ph. D. (Psychology)) -- University of Limpopo, 2019
Keywords: Dark tetrad personality types; Infidelity; Sexual aggression; Adversarial sexual beliefs; Ambivalent sexism; Socio-sexuality; Personality -- Social aspects; Personality disorders -- South Africa -- Limpopo; Typology (Psychology); Psychoanalysis; African students